1996
DOI: 10.1074/jbc.271.12.7196
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Free and Esterified Cholesterol Absorption in Cholesterol Esterase (Bile Salt-stimulated Lipase) Gene-targeted Mice

Abstract: The involvement of pancreatic cholesterol esterase (bile salt-stimulated lipase) in cholesterol absorption through the intestine has been controversial. We have addressed this issue by using homologous recombination in embryonic stem cells to produce mice lacking a functional cholesterol esterase gene. Cholesterol esterase knockout mice and their wild type counterparts were fed a bolus dose of [3H]cholesterol and a trace amount of [beta-14C]sitosterol by gavage. The ratio of the two radiolabels excreted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 48 publications
8
118
0
1
Order By: Relevance
“…These numbers agree well with those obtained by other investigators. 22 Food intake of WT and KO mice did not show any significant difference during this study (data not shown).…”
Section: Cholesterol Uptakementioning
confidence: 64%
“…These numbers agree well with those obtained by other investigators. 22 Food intake of WT and KO mice did not show any significant difference during this study (data not shown).…”
Section: Cholesterol Uptakementioning
confidence: 64%
“…Bile salt-stimulated cholesterol esterase activity, which could be inhibited by antibodies specific for the pancreatic enzyme, was also reported to be present in human serum and in the aorta (16,17). These results suggested that bile saltstimulated cholesterol esterase may have a systemic origin and participates in systemic lipid metabolism, in addition to its role for nutrient digestion and transport in the gastrointestinal tract (43).…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 81%
“…Studies of CEL knockout mice show that lack of CEL appears to have no effect on the intestinal absorption of unesterified fat. 3,4 However, the cholesteryl ester hydrolytic activity is unique to CEL in the digestive tract, and CEL has been suggested to function as a supplementary enzyme to ensure effective hydrolysis of triglycerides and phospholipids. 5 The C-terminal part of CEL consists of a unique structure with proline-rich O-glycosylated repeats of 11 amino-acid residues each.…”
Section: Introductionmentioning
confidence: 99%